AFFIRMATIVE ACTION DAN PENGUATAN PARTISIPASI POLITIK KAUM PEREMPUAN - Rahmatunnisa, Mudiyati (JWP (Jurnal Wacana Politik), 2016)
Despite various existence of ratified UN Conventions and other international and national policies, womenâs political participation has still been considered week. They remain substantially underrepresented in the position of political decision making. In other words, political sphere is still male-dominated. Needless to say, formal political equality statements are not enough. It needs more actions to make it into reality. One potential measure, among other things, is affirmative action in the form of gender quota. The policy has the potential to strengthen womenâs political participation and representation. Nevertheless, empirically, this has not always been the case. As one would expect, there are a number of factors which determine the effectiveness of the policy implementation process, i.e., political, socio-economic, and socio-cultural. For more effective implementation, affirmative action policy needs to be accompanied by parallel effort of handling those hindrances.Â